Estudio del proceso fermentativo del cacao nacional (Theobroma cacao) considerando distintos tipos y su incidencia en las características físico-químicas y sensoriales" - Aldas Morejón, Jhonnatan Placido (2020)
The aim of the present research work is to study the fermentation process of the Ecuadorian cacao (Theobroma cacao). For this purpose, there have been considered different types of cocoa and their impact on the| physical-chemical and sensory characteristics. or development, 5 kg of each sample was fermented for 5 days, with removals (24, 48, 24, 24 hours) controlling temperatures and to finish a drying in the sun until reaching a humidity of 7 %. Two statistical packages were used, the first one was applied to evaluate the variability that existed between cocoa types (factor A) and fermentation days (factor B/A), consisting of 12 treatments and 3 repetitions with a total of 36 experimental units. Determined in this way, according to the results that the days of fermentation have a significant impact on the changes of the studied variables, followed by the types of cocoa that do not vary widely. At the same time, the type and morphology of yeast were identified from the mucillake of the areas under study. For the second design, a trifactorial A* B * C was applied to determine the physical-chemical and sensory characteristics of processed cocoa, where it was structured as: Fermentation method (factor A); Cocoa type (factor B) and Study area (factor C) with 18 treatments and 3 repetitions obtaining a total of 54 experimental units. Demonstrating the treatment a2b0c1 (Controlled fermentation + Criollo + Canton Baba) was the best in the variables titratable acidity and seed index followed by the other interactions that were highlighted in pH almonds and fermentation index. In addition, it showed better intensity in the profiles: Aroma, acidity, bitterness, astringency, aftertaste, flavor categories: Cocoa, nut, fresh fruits and floral obtaining an outstanding quality. Complying with permissible limits of heavy metals, alkaloids, lipid profile and microbiological. Therefore, it is a postharvest treatment recommended for the process of cocoa, obtaining a harmless chocolate with nutritional properties, being an excellent source of energy for its carbohydrate and sugar content. Keywords: Fermentation, Cocoa, Treatment, Chocolate, Quality.